2010
DOI: 10.3340/jkns.2010.47.3.199
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Results of Balloon Kyphoplasty Performed at Different Times after Injury

Abstract: Objective : Balloon kyphoplasty is a minimally invasive procedure that is mainly performed for refractory pain due to osteoporotic compression fractures. The purpose of this study was to evaluate the results of balloon kyphoplasty performed at different times after an injury. Methods : In this retrospective study, the records of 99 patients who underwent one level of balloon kyphoplasty between January 2005 and December 2007 were reviewed. The patients were divided into three groups : 21 patients treated withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
1
9
0
2
Order By: Relevance
“…Two additional retrospective studies on 72 and 99 patients who were treated with kyphoplasty also reported better restoration in patients who were treated within 2 months after injury. However, one study only reported absolute numbers for each group itself, but did not statistically examine if the differences between the groups were significant and therefore did not allow any reliable conclusions [22]. The other study only reported a better preservation of the anterior vertebral and kyphotic angle in the early group, but did not find significant absolute differences [23].…”
Section: Discussionmentioning
confidence: 98%
“…Two additional retrospective studies on 72 and 99 patients who were treated with kyphoplasty also reported better restoration in patients who were treated within 2 months after injury. However, one study only reported absolute numbers for each group itself, but did not statistically examine if the differences between the groups were significant and therefore did not allow any reliable conclusions [22]. The other study only reported a better preservation of the anterior vertebral and kyphotic angle in the early group, but did not find significant absolute differences [23].…”
Section: Discussionmentioning
confidence: 98%
“…In a reverse conclusion, a long conservative treatment attempt might actually reduce the benefit of a subsequent kyphoplasty and cause sustained postural disadvantages to the patient as fracture consolidation hinders LKA restoration. However, there is no consistent data available yet regarding the influence of surgical timing on vertebral height restoration [20][21][22] . www.nature.com/scientificreports www.nature.com/scientificreports/ Apart from the radiographic benefits of the operation, we also observed a significant pain reduction in our patients postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Infact, as soon as the balloon is deflated, there is often a new total or partial vertebral body collapse. [232425262728] This has led to new devices creation. They allow the vertebral height recovery.…”
Section: Discussionmentioning
confidence: 99%